THE REFUSAL AGAINST 1925 TEACHER ORDINANCE IN WEST SUMATRA: ITS CONDITIONS, COURSE, AND AFTERMATH - Muhammad Yuanda Zara (Mozaik: Kajian Ilmu Sejarah, 2018)
Worried with the rise of modernist Muslim movement coming from the Middle East, in 1925 Netherlands Indies Government issued and applied Teacher Ordinance (Goeroe Ordonnantie) in several regions in Netherlands Indies. It stipulated, among others, that every Muslim teacher must report himself to district head so that the district head could immediately issue a letter of identification, that Islamic teachers must keep the list of their students and religious subjects given to them, and the situation in which the right of teaching would be canceled, for example if the Islamic teachers provoke their students to condemn the Government. The Ordinance had been successfully applied and the Government planned to extend it to other regions, including West Sumatra. Yet, the majority of Islamic teachers throughout West Sumatra refused the plan. The refusal against 1925 Teacher Ordinance, in the form of mass demonstration and negotiation, influenced almost all of Islamic teachers in West Sumatra and reduced existing social and religious gaps in Minangkabau society due to the same feeling of dissatisfaction. Eventually, the Government canceled the application plan of the Ordinance in West Sumatra, showing the effectiveness of the social movement organized by Islamic teachers in West Sumatra. Keywords: Teacher Ordinance, social movement, Islamic teachers, West Sumatera, Islam and colonialism